PENERAPAN MODEL PEMBELAJARAN TWO STAY TWO STRAY BERBANTUAN MEDIA REALIA UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS V SD - Azizah, Fadillah; Rahmi, Putri (STKIP Persada Khatulistiwa Sintang, 2025)
This study aimed to investigate the improvement of fifth-grade students’ learning outcomes at SDN Ujong Kuta, Aceh Besar, through the implementation of the Two Stay Two Stray learning model assisted by realia media. The research employed Classroom Action Research (CAR) consisting of two cycles, each including planning, implementation, observation, and reflection stages. The subjects were 25 fifth-grade students, comprising 14 boys and 11 girls. Teacher and student activities were observed using observation sheets, while learning outcomes were measured through test sheets. The results revealed an increase in teacher activity from 70.83% in cycle I to 90.62% in cycle II, and student activity from 66.66% to 89.58%. Students’ learning outcomes also improved from 65.00% in cycle I to 87.50% in cycle II. These findings indicate that the Two Stay Two Stray learning model assisted by realia media is effective in enhancing both student engagement and learning outcomes in fifth-grade students at SDN Ujong Kuta, Aceh Besar.